Managerial Perceptions of the Impact of HRIS on Organizational Efficiency - Kumar, Nikhal Aswanth (Journal of Economics and Behavioral Studies, 2013)
This study evaluates the impact of the HRIS system on HR functions, time management, cost management, managerial satisfaction and organizational efficiency. A sample of 101 managers was drawn from a Municipality in South Africa using cluster sampling. Data was collected using a selfdeveloped, closed-ended questionnaire comprising of 28 items, the psychometric properties (validity, reliability) of which was statistically assessed using Factor Analysis and Cronbach’s Coefficient Alpha respectively. Data was analyzed using descriptive and inferential statistics. The results indicate that managers have a fairly positive view of the impact of the HRIS on organizational effectiveness with the greatest degree of confidence being placed on the impact of HRIS on time management and on HR functions. The results confirm that a well implemented and managed HRIS enables readily available information to be translated into more information sharing, greater knowledge transfer and management. Consequently, the HRIS has the potential to enhance the speed and quality of decision making and the realisation of the HR strategy, thereby enhancing organizational effectiveness.